Candida rugosa lipase for the biodiesel production from renewable sources. (December 2020) - Iuliano, Mariagrazia; Sarno, Maria; De Pasquale, Salvatore; Ponticorvo, Eleonora
Abstract: Lipase from Candida rugosa was physically attached to Mg modified Fe2 O4 nanoparticles (NPs) and employed for the conversion of brewers' spent grains (BSGs) into biodiesel, in the presence of methanol. The proposed strategy explored the direct immobilization of the enzyme on the as-prepared oleic acid modified inexpensive NPs. In addition, a large amount of enzyme was bound on the NPs, allowing their efficient recycling by using an external magnet. A very remarkable better yield of 98% was achieved at 1:4 oil/methanol molar ratio after 48 h at 45 °C reaction temperature. The nanocatalyst also exhibits good recyclability. The biodiesel produced was analyzed according to EN 14214. Graphical abstract: Image 1 Highlights: Multi Physico-chemical interaction on cheap MgFe2 O4 oleic acid-functionalized NPs. Candida rugosa lipase high payload, stability, and activity. Role of time, molar ratio, concentration, temperature and cycles of reuse. Biodiesel from brewers' spent grains oil in agreement with EN 14214.